Assessing the infectious reservoir of falciparum malaria: past and future. Issue 7 (July 2015) - Stone, Will; Gonçalves, Bronner P.; Bousema, Teun; Drakeley, Chris
Highlights Malaria control and elimination could be enhanced by targeting human-to-mosquito transmission of the parasite. A better understanding of which individuals in endemic populations infect mosquito vectors would improve targeting. Studies that directly assessed the human infectious reservoir of malaria using xenodiagnostic approaches are critiqued. Future direct assessments of infectious reservoir should consider factors affecting transmission potential, longitudinal infectivity to mosquitoes, and exposure to vectors.